Experiences of veterinary medicine intervention in the development of Healthy Municipalities in Latin America and in the Caribbean - Estela-Galarza, María (2022)
The aim of this study was to identify the areas of participation of veterinarians, framed within their training and professional skills in the development of Healthy Municipalities. A bibliographic search was carried out to collect the activities carried out in the Healthy Municipalities and health promotion strategies articulated to them at the level of Latin America and the Caribbean. The study found that the veterinarian has the necessary professional skills to intervene and lead in the various activities within the areas of food safety – animal production, public health, animal health and environmental health – conservation of biodiversity in the framework of development of the Healthy Municipalities strategy. These competencies can also be developed through the strategies articulated to the following Healthy Municipalities: Healthy Neighbourhoods, Healthy Schools, Healthy Spaces, Healthy Frontiers, Green and Healthy Hospitals, Healthy Markets, Productive Municipalities, Healthy Parks, Healthy Universities and Healthy Homes. It is concluded that the veterinarian has professional skills capable of developing multiple functions within the Healthy Municipalities programmes and articulated strategies to these, therefore his participation is necessary.